Therapy of malignant ascites in vivo by 211At-labelled microspheres - Bredow, J.; Kretzschmar, M.; Wunderlich, G.; Dörr, W.; Pohl, T.; Franke, W.-G.; Kotzerke, J. (Nuklearmedizin - NuclearMedicine, 2004)
Aim: Determination of the biological effect of the alpha emitter 211At on cellular level as well as the assessment of dosimetric data in a tumour model in vivo. Methods: Transplantation of malignant ascitic cells in mice intraperitoneally and estimation of tumour characteristics (doubling time of the cells, mean survival of the animals following an i.p. application of a defined tumour cell number). 211At labelled human serum albumine microspheres B-20 (MSP) of variing activity were injected into tumour bearing mice intraperitoneally. The effectiveness of the therapy was evaluated by means of determination of the duration of cell cycle arrest as well as the microscopic analysis of the rate of abnormal mitotic cells due to radiation induced damage. Furthermore, dose dependence of survival was evaluated. Results: Three days following the intraperitoneally application of 8 x 106 tumour cells, 50-600 kBq 211At-MSP were applied into the abdominal cavity. Considering the volume of ascites at this time and the administered activity, dose calculations were performed. An activity of 50 kBq caused a dose of 0.84 Gy. The increase of radiation induced effect on ascitic tumour cells was correlated with the dose. Between the duration of the cell cycle arrest and the administered activity, a directly proportional correlation was found. The mean survival of non-treated animals was 16.9 ± 3.7 days. The prolongation of the survival was proportional to the activity administered. Using a dosage of 10 Gy, five animals out of 16 survived. Conclusion: Therapy of malignant ascitic cells using 211At-MSP was effective in vivo. For tumour therapy, the 211At represents a highly effective alternative to usually applied beta emitters.
Keywords: 211Astatine; microspheres; Ehrlich mouse ascites carcionoma; radionuclide therapy